Design of a low-voltage input-output rail-to-rail CMOS buffer - Yang, Wenjie (2008)
The objective of this project is to design a buffer, which is able to work below a supply of 1.5 V typical and remain in operation even at 1.2 V or lower in the worst case for use in bond pad designs.